GESTÃO DOCUMENTAL E DA MEMÓRIA DO PODER JUDICIÁRIO: o programa do Conselho Nacional de Justiça - Carlos Alexandre Böttcher; Ingrid Schroder Sliwka (TRF2, 2020)
This paper's main goal is to analyse the importance of the "Records Management and Memory Programme" instituted by the Brazilian National Council of Justice. Its methodology departs from the constitutional and legal primary sources that support the Programme. Then it proceeds by examining the normative acts issued by the National Council of Justice to present the Programme's historical development. Further on, this paper makes a description and brief theoretical analysis of the main issues regarding the subject and its current regulation. Ithighlights as well the historical archives as part of the national cultural heritage. In the end, the paper summarizes today's state of affairs of the Programme establishing considerations and challenges for Records and Memory management in the Brazilian Judicial Branch.